Brand triangle model to avoid branding myopia - Lencastre, Paulo de (2014)
This article takes the metaphor of myopia to explain the most limited vision of brand, understood as the identifying sign of a product. As brand is a sign, we turn to semiotics, the science of signs, in order to apply a model which broadens the concept of brand to three dimensions: that of the identity sign itself, that of the object the sign refers to and that of the response of the market to the sign.